A novel knotless hand-sewn end-to-end anastomosis using V-loc barbed suture vs. stapled anastomosis in laparoscopic left colonic surgery: A propensity scoring match analysis - Xu, Shining; Zhao, Xuan; He, Zirui; Yang, Xiao; Ma, Junjun; Dong, Feng; Zang, Lu; Fingerhut, Abe; Zhang, Luyang; Zheng, Minhua (Frontiers in Surgery, 2022)
Background Laparoscopic colectomy is widely practiced for colon cancer, but many variations exist for anastomosis after laparoscopic colon cancer radical resection. Method We retrospectively analyzed 226 patients who underwent laparoscopic-assisted radical resection for left colon cancer with knotless hand-sewn end-to-end anastomosis (KHEA) technique with barbed V-loc™ suture material and compared perioperative outcomes, safety, and efficacy to those undergoing stapled anastomosis from 2010 to 2021. Results After the 1:2 propensity score matching, 123 participants with similar preoperative characteristics (age, body mass index, TNM stage, and tumor location) were enrolled in the study: 41 in the KHEA and 82 in the stapler group. Statistically significant differences were found in time to accomplish the anastomosis (mean 7.9 vs. 11.9 min, p < 0.001) and hospital costs (mean 46,569.71 vs. 50,915.35 CNY, p < 0.05) that differed between the KHEA and stapler group, respectively. No statistically significant difference was found in the mean delay to bowel function recovery (2.6 vs. 2.7 days, p = 0.466), duration of hospital stay (8.6 vs. 7.9 days, p = 0.407), or rate of postoperative complications (14.6% vs. 11.0%, p = 0.563). Anastomotic leakage occurred in 11 patients: 5 (12.2%) vs. 6 (7.3%) (p > 0.05) in the KHEA and stapler group, respectively. Conclusion KHEA is feasible and safe for anastomosis after laparoscopic left hemicolectomy. The KHEA technique could reduce operation time and hospital costs with complication rates comparable to stapling.